RELEVANSI NILAI TINGKAT LABA VS PERUBAHAN LABA - Ari Budi Kristanto (Jurnal Riset Akuntansi Terpadu, 2019)
This study aims to examine whether the level of earnings and changes in earnings have the information value relevance, and test whether there is a difference in the value relevance between the two types of information. This study uses companies that are included in the manufacturing industry group on the IDX between 2009-2016 as an object of observation. The sample used was chosen using the purposive sampling method, with criteria: registered in a row over an 8-year period, having complete data for all research variables. The existence of value relevance is tested using multiple regression analysis tools, to see indications of the ability of information to influence stock prices as a proxy for investor decisions. Moreover, the difference in the value relevance of information is tested by evaluating the difference in the residuals of the two regression models using the Hotelling t score. The results of this study indicate that there is value relevance to earnings level information and earnings changes, but it cannot prove that the relevance of information values is significantly different. Allegedly, information on the level of earnings and changes in earnings both represent management performance, so that the meaning of both information is not significantly different and equally utilized to support investor decision making.